2020
DOI: 10.1093/icvts/ivaa288
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific computational fluid dynamics analysis of transcatheter aortic root replacement with chimney coronary grafts

Abstract: OBJECTIVES Transcatheter aortic root repair (TARR) consists of the simultaneous endovascular replacement of the aortic valve, the root and the proximal ascending aorta. The aim of the study is to set-up a computational model of TARR to explore the impact of the endovascular procedure on the coronary circulation supported by chimney grafts. METHODS Computed tomography of a patient with dilated ascending aorta was segmented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The blood ow satis es the Navier-Stokes equation, in which the blood density (ρ) is 1060 kg/m3 and the blood viscosity coe cient is µ. 0.0035 kg/ms, the number of iterations is 500, the time step is 0.001 s, and the maximum number of iterations is 50 [17].…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…The blood ow satis es the Navier-Stokes equation, in which the blood density (ρ) is 1060 kg/m3 and the blood viscosity coe cient is µ. 0.0035 kg/ms, the number of iterations is 500, the time step is 0.001 s, and the maximum number of iterations is 50 [17].…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…The blood ow satis es the Navier-Stokes equation, in which the blood density (ρ) is 1060 kg/m3 and the blood viscosity coe cient is μ. 0.0035 kg/ms, the number of iterations is 500, the time step is 0.001 s, and the maximum number of iterations is 50 [27].…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…However, the need to search for new materials for the formation of aortic prostheses is still relevant. Dacron valve-containing conduits are most often used for ascending aorta and aortic valve replacement [5]. Various methods of preoperative preparation of the Dacron tube have also been proposed to reduce bleeding, however, these techniques made the prosthesis rigid and more rigid, which made it difficult to create anastomoses, especially with the orifices of the coronary arteries [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent references are suggested on complications and reoperations in ascending aortic aneurysm shows that a leaky anastomosis is the cause of bleeding, and then the formation of pseudoaneurysms and fistulas. Along with the improvement and widespread use of artificial prostheses for replacing the affected aorta, another original direction, the use of biological tissue was further developed [5,6]. However, experience has shown that the problem of an "ideal" prosthesis has not yet been solved and it is necessary to continue the search for new options for implanting artificial conduits to prevent complications.…”
Section: Introductionmentioning
confidence: 99%